The Effectiveness of Stimulation to The Toilet Learning Abilities of Toddler - Maria Ulfa (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2018)
Toilet learning in children is an attempt to train children to be able to control in defecating and urinating. The aim of this research was to determine the effectiveness of stimulation to the toilet learning ability of toddler. The research usedPre-Experimental One-Group Pre-test-post test design. The sampling technique used purposive sampling. The statistical test used wilcoxon signed rank test. The population was 14 toddler of PosyanduBendowulungKabupatenBlitar. The result showed that there was an effect of stimulation to the ability of toilet learning of 1 to 3 years old toddler. The Statistical test result using Wilcoxon sign rank test obtained p value = 0,000 (<0,05). It is expected to increase knowledge about the implementation of toilet learning stimulation, especially for parents to make their children more indepen- dent.